Disparate Practice Patterns and Survival Outcomes: The Impact of Centralization of Cancer Care for Adrenocortical Carcinoma in the United States. Issue 4 (25th October 2021) - Stone, Benjamin V.; Tallman, Jacob E.; Moses, Kelvin A.
Abstract : Purpose: Adrenocortical carcinoma is a rare but aggressive malignancy. While centralization of care to referral centers improves outcomes across common urological malignancies, there exists a paucity of data for low-incidence cancers. We sought to evaluate differences in practice patterns and overall survival in patients with adrenocortical carcinoma across types of treating facilities. Materials and Methods: We identified all patients diagnosed with adrenocortical carcinoma from 2004–2016 in the National Cancer Database. The Kaplan-Meier method was used to evaluate overall survival and multivariable Cox regression analysis was used to investigate independent predictors of overall survival. The chi-square test was used to analyze differences in practice patterns. Results: We identified 2, 886 patients with adrenocortical carcinoma. Median overall survival was 21.8 months (95% CI 19.8–23.8). Academic centers had improved overall survival versus community centers on unadjusted Kaplan-Meier analysis (p <0.05) and had higher rates of adrenalectomy or radical en bloc resection (p <0.001), performed more open surgery (p <0.001), administered more systemic therapy (p <0.001) and had lower rates of positive surgical margins (p=0.03). On multivariable analysis, controlling for treatment modality, academic centers were associated with significantly decreased risk of death (HR 0.779, 95% CI 0.631–0.963, p=0.021). Conclusions: Treatment of adrenocortical carcinoma at an academic center is associated with improved overall survival compared to community programs. There are significant differences in practice patterns, including more aggressive surgical treatment at academic facilities, but the survival benefit persists on multivariable analysis controlling for treatment modality. Further studies are needed to identify the most important predictors of survival in this at-risk population.